Longitudinal changes of lactopontin (milk osteopontin) in term and preterm human milk - Zhu, Jing; Yu, Xue; Wang, Yiran; Bai, Shasha; Lai, Jianqiang; Tong, Xiaomei; Xing, Yan (Frontiers in Nutrition, 2022)
Abstract: Background: Lactopontin (LPN) in breast milk, also known as milk osteopontin is thought to play a myriad of im-portant roles in infants when they are immature. The purpose of the present study was to examine the longitudinal changes in LPN concentrations in term and pretrm milk, and elucidate the links between maternal characteristics, LPN levels, and child growth in a birth cohort. Methods: 131 mothers who delivered term, moderate-late preterm (MPT), very preterm (VPT) and ex-tremely preterm (EPT) infants were included, milk samples were collected at 7, 14, 28 and 120 days postpartum. LPN concen-tration was determined by multiple reaction monitoring (MRM) using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Results: Our results indicated that LPN change over time of VPT (P=0.024) and EPT (P=0.003) were significantly different from term milk, although they all gradually decreased with lactation. In terms of LPN-related fac-tors, maternal age was a significant contributor in late mature milk and pre-pregnancy BMI a significant contributor to colos-trum and transitional milk. We further investigated relationships between LPN levels and infant weight and our results suggest-ed that high levels of LPN in breast milk might be useful for the catch-up growth of infants. Conclusions: LPN levels in breast milk are related to maternal factors, and differences in LPN levels may affect the growth of infants. As milk is a critical part in the mother–breastmilk–infant ‘triad’, the association between maternal-infant factors and milk LPN levels warrants further study.